2006
DOI: 10.1002/eat.20336
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic body image in bulimia nervosa: Mental representation of body dimensions and biological motion patterns

Abstract: Objective: The aim of the present study was to find out whether in bulimia nervosa the perceptual component of a disturbed body image is restricted to the overestimation of one's own body dimensions (static body image) or can be extended to a misperception of one's own motion patterns (dynamic body image).Method: Participants with bulimia nervosa (n ¼ 30) and normal controls (n ¼ 55) estimated their body dimensions by means of a photo distortion technique and their walking patterns using a biological motion di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 47 publications
5
57
0
1
Order By: Relevance
“…The present data also shows that by improving body image, the cognitions relating to the disturbed eating behaviour are also reduced, even though the frequency of binge eating behaviour and the degree of restraint eating style were not reduced by a statistically significant level. This indicates that body image therapy alone cannot improve the disturbed eating pattern, but it may be a worthy complementation to standardised eating disorder treatment programmes (see also Vocks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data also shows that by improving body image, the cognitions relating to the disturbed eating behaviour are also reduced, even though the frequency of binge eating behaviour and the degree of restraint eating style were not reduced by a statistically significant level. This indicates that body image therapy alone cannot improve the disturbed eating pattern, but it may be a worthy complementation to standardised eating disorder treatment programmes (see also Vocks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Body image as a theoretical construct, is thought to be multidimensional consisting of perceptual, cognitive, affective and behavioural components (Thompson, 2004). Dysfunction in one or more component can lead to specific effects such as: Overestimation of one's own body dimensions, (Cash and Deagle, 1997;Farrell, Lee, & Shafran, 2005;Vocks, Legenbauer, Rüddel, & Troje, 2007), negative feelings and thoughts towards the body (Cooper & Fairburn, 1992;Tuschen-Caffier, Vögele, Bracht, & Hilbert, 2003;Vocks, Wächter, Wucherer, & Kosfelder, 2008), as well as body avoidance and checking behaviour (Reas, Whisenhunt, Netemeyer, & Williamson, 2002;Rosen, Srebnik, Saltzberg, & Wendt, 1991;Shafran, Fairburn, Robinson, & Lask, 2004). Consequently, in the therapy of eating disorders, specific interventions for the improvement of body image are of interest (Fernandez, Turó n, Siegfried, Meermann & Vallejo, 1995;Vandereycken, Depreitere & Probst, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that women with AN and BN seem to overestimate their own body dimensions to a similar degree, whereas healthy women show a tendency to underestimate them. 5,6 The cognitiveaffective component of a disturbed body image comprises negative body-related attitudes and emotions. Although in Western cultures, discontent with one's shape and weight seems to be widespread in the general female population, 7 women with eating disorders exceed healthy women in terms of body dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The perceptive component primarily involves the mental representation of one's own body. Healthy women, for example, tend to underestimate the size of their body [7] whereas patients with eating disorders often overestimate its dimensions [8,9]. …”
Section: Introductionmentioning
confidence: 99%